The EU’s stability-democracy dilemma in the context of the problematic accession of the Western Balkan states - Smith, Nicholas Ross; Markovic-Khaze, Nina; Kovacevic, Maja (Routledge, 2020)
The accession of the remaining six Western Balkan states into the EU is shrouded in much uncertainty. Despite Croatia finally traversing the difficult path to eventual membership in 2013, not one of the remaining Western Balkan countries can claim to be on a definite pathway to membership today. An increasingly prevalent argument is that the EU’s engagement with its neighbourhoods has faltered because its strategies have been undermined by an inherent stability-democracy dilemma. This article examines the EU’s engagement with the Western Balkans and finds that although the EU tried to transcend this dilemma, in reality, a tension between stability and democracy was present with the former generally receiving more attention in policymaking. This led to not only a lack of tangible democratization amongst the Western Balkan states, but further uncertainty about their accession prospects. By 2018, it was clear that the EU’s engagement with the Western Balkans needed a rethink, resulting in a new approach: the ‘Six Flagship Initiatives’. However, given the apprehensiveness of some member states (especially France) coupled with the presence of outsiders such as Russia and China in the area, the accession prospects of the six non-EU Western Balkan states remains blurred.